Factores asociados al estrés laboral en el personal de enfermería del hospital general IESS Babahoyo, período noviembre 2023 – abril 2024 - Bermudes Sánchez, Maireth Nohelia (2024)
The research carried out at the IESS Babahoyo General Hospital aims to analyze the factors related to work stress among nursing staff, with the general objective of identifying possible interventions to improve their well-being and mental health. The methodology used involved the administration of a survey instrument to a sample of 80 people, through which factors such as the availability of resources and the resilience of the nursing staff were evaluated. Findings indicated a high prevalence of work-related stress among nursing professionals, with the majority reporting significant levels of stress. It was observed that the lack of qualified personnel and the high workload represented the primary factors that influenced the presence of stress in the workplace. Additionally, occupational stress was observed to be related to a variety of physical, emotional, and cognitive symptoms that may have an adverse impact on the health and ability of nursing professionals to provide optimal care. The pressing need to implement interventions and policies aimed at enhancing the well-being and mental health of nursing staff is emphasized. It is advisable to implement training programs focused on stress management, address staff shortages and work overload, and review organizational policies to cultivate a work environment that prioritizes the balance between workload and employee well-being. The study highlights the importance of addressing work-related stress in nursing staff by identifying key factors and presenting practical recommendations to improve working conditions and promote the well-being of nursing professionals in hospital settings.